Density, characterization and efficiency of Nitrogen fixing bacteria in areas of degraded caatinga - Almeida, Aldênia Mendes Mascena de; Mendes Filho, Paulo Furtado; Garcia, Kaio Gráculo Vieira; Gomes, Vânia Felipe Freire; Almeida, Cicero Lima de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Soil degradation resultant from non-conservation practices may lead to irreparable damage to the chemical and biological properties of the soil system of semi-arid regions of northeastern Brazil. The aim of this work was to evaluate soil chemical attributes, estimate the population density of native rhizobia strains and isolate efficient strains in symbiotic N2 fixation in the cowpea bean in exclusion of super grazing areas. The study was carried out at Farm Formigueiro, located in the municipality of Irauçuba, Ceará, Brazil. The soil samples were collected in two areas characterized by different levels of degradation, being: i) area of exclusion and ii) area of super grazing.The experimental design was completely randomized with eight treatments and four replications, being a control with addition of mineral nitrogen C (+ N-R); and one with omission of mineral nitrogen and absence of C (-N-R) inoculation, totalizing 32 experimental units. The intensive use of the soil and the management history of the studied areas contributed negatively to the chemical properties and density of rhizobian cells. The study of the N2 fixing efficiency of the native strains in the exclusion and super pasture areas evidenced the occurrence of strains with variable efficiency, presenting a symbiotic efficacy around 22 to 41% for the cowpea beans.